Method for preparing carbon quantum dots by taking coal gasification fly ash as raw material

Through a two-step method of pre-oxidation and hydrothermal reaction of coal gasification fly ash, it was successfully converted into high value-added carbon quantum dots, solving the problem of utilizing coal gasification fly ash and achieving resource recycling, economy and environmental protection. production effect.

CN119330344APending Publication Date: 2025-01-21XINJIANG UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411510006.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art is difficult to effectively utilize coal gasified fly ash and convert it into high value-added carbon quantum dots, resulting in solid waste emissions and waste of resources.

Method used

Use two -step legal carbon quantum dot: first of all, pre -oxidation treatment of gasification fly ash, and then perform water heating reactions in the water thermal reaction kettle. Through a series of post -treatment steps, solid carbon quantum dots are finally obtained.

Benefits of technology

The carbon-containing components in coal gasification fly ash were successfully converted into carbon quantum dots with fluorescent properties, realizing high-value utilization of solid waste, reducing waste emissions, and improving the comprehensive utilization rate of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330344A_ABST
    Figure CN119330344A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing carbon quantum dots by taking coal gasification fly ash as a raw material. Coal gasification fly ash is used as a raw material, is an industrial by-product and is generally regarded as waste. By using the raw materials, not only is the production cost reduced, but also resource utilization of wastes is realized, and the method has dual advantages of environment and economy. The method comprises the following steps: carrying out simple oxidation pretreatment on waste gas fly ash generated after industrial coal gasification, then transferring the waste gas fly ash to a hydrothermal reaction kettle, and carrying out centrifugation, filtration and dialysis to obtain the fluorescent carbon quantum dots. Compared with a traditional carbon quantum dot preparation method, the method has the advantages that use of harmful chemical substances is reduced, use of strong oxidizing acid such as concentrated sulfuric acid and concentrated nitric acid is avoided, and therefore environmental pollution and safety risks are reduced. Meanwhile, the used two-step method (pre-oxidation treatment and hydrothermal reaction) is relatively simple and easy to control, and the yield and quality of the carbon quantum dots can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The invention specifically relates to a method for preparing carbon quantum dots, and belongs to the field of carbon nanomaterials. Background Art

[0002] Carbon Quantum Dots (CQDs) are a class of zero-dimensional carbon-based nanomaterials with a size of less than 10 nanometers. Due to their unique physical and chemical properties, they have shown great application potential in many fields such as biomedicine, optoelectronics, and sensors. CQDs are composed of surface groups and carbonaceous cores. The surface groups usually contain oxygen-containing functional groups such as hydroxyl and carboxyl, while the carbonaceous core is mainly composed of sp2 and sp3 hybridized carbon atoms, forming structures such as amorphous carbon, graphite crystallites or graphene fragments. Compared with traditional semiconductor quantum dots, CQDs have the advantages of low toxicity, good biocompatibility, excellent photostability, adjustable luminescence wavelength, and easy surface functionalization. The synthesis methods of CQDs are mainly divided into two strategies: "top-down" and "bottom-up". The "top-down" method usually starts from macromolecular carbon materials such as graphite, graphene or carbon nanotubes, and prepares CQDs through chemical oxidation or physical etching; while the "bottom-up" method starts from small molecule precursors and synthesizes CQDs through reactions such as dehydration and carbonization.

[0003] Coal gasification fly ash is solid waste generated in the coal gasification industrial process, usually in granular or powdery form. This fly ash contains unreacted carbon and minerals and has potential utilization value. The present invention aims to convert coal gasification fly ash into high value-added carbon quantum dots, which not only reduces the emission of solid waste, but also realizes the recycling of resources and improves the comprehensive utilization rate of resources. The chemical structure of coal gasification fly ash is similar to the carbonaceous core of CQDs, making it an ideal CQDs precursor material. Through the method of the present invention, the carbon-containing components in coal gasification fly ash can be effectively converted into carbon quantum dots with fluorescent properties, which provides a new way for the high-value utilization of solid waste. Summary of the invention

[0004] The present invention provides a method for preparing carbon quantum dots. The method adopts a "two-step method". First, the coal gasification fly ash is pre-oxidized, and then the treated product is transferred to a hydrothermal reactor for hydrothermal reaction. Through a series of post-treatment steps, including reduced pressure distillation, filtration, centrifugation, dialysis and freeze-drying, solid carbon quantum dots are finally obtained.

[0005] The method for preparing carbon quantum dots comprises the following steps:

[0006] Step 1: Mix the coal gasification fly ash and the selected oxidant in a mass ratio of 1:1 to 1:5, add the mixture into a beaker filled with distilled water, and perform ultrasonic treatment for 20 to 40 minutes at room temperature and pressure to promote uniform mixing of the oxidant and the fly ash to form a reaction solution A;

[0007] Step 2: adjusting the pH of the reaction solution A to neutral, and then removing the insoluble matter that may be produced during the reaction by vacuum filtration to obtain a clear reaction solution B;

[0008] Step 3, transferring the reaction solution B to a hydrothermal reactor, and performing a hydrothermal reaction at a set temperature and pressure to promote the formation of carbon quantum dots;

[0009] Step 4. After the reaction is completed, the substances in the reactor are naturally cooled to room temperature, then the reactor is opened, and the obtained carbon dot solution is filtered through a 0.2μm water-based microporous filter membrane to remove larger particles, followed by dialyzing using a dialysis bag with a molecular weight cutoff of 3500Da to remove small molecule salts and other impurities, and finally the dialyzed solution is concentrated by vacuum distillation, and solid carbon quantum dots are obtained by freeze-drying technology.

[0010] The coal gasification fly ash in step 1 may be any one of anthracite gasification fly ash, bituminous coal gasification fly ash or lignite gasification fly ash to adapt to different industrial by-products.

[0011] The oxidant in step 1 may be persulfate, potassium ferrate or perchlorate to provide an oxidizing environment and promote the formation of carbon quantum dots.

[0012] The ultrasonic treatment in step 1 preferably has a frequency of 20 to 40 kHz and a treatment time of 0.5 to 2 hours to ensure sufficient dispersion and reaction.

[0013] The neutralization treatment in step 2 can use sodium carbonate, potassium hydroxide, sodium hydroxide, sodium bicarbonate or ammonia water to adjust the pH value of the solution to neutral.

[0014] The vacuum filtration in step 2 preferably uses a 0.2 μm water filter membrane to ensure that the filtrate does not contain large insoluble particles.

[0015] The hydrothermal reaction temperature in step 3 is preferably 160-190° C., and the reaction time is preferably 5-7 hours to ensure sufficient generation of carbon quantum dots.

[0016] The molecular weight cut-off of the dialysis bag in step 4 is 3500Da to ensure the removal of small molecule impurities.

[0017] The principle of the method of the present invention is based on the microstructural characteristics of coal gasification fly ash, which contains amorphous carbon regions and nano-scale crystalline carbon regions. Under the action of an oxidant, the crystalline carbon regions are easily oxidized to form nano-sized carbon quantum dots with fluorescent properties.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The present invention utilizes coal gasification fly ash to fully utilize the waste generated during the coal gasification process, which helps to reduce the generation of waste. The preparation of carbon dots will not only reduce production costs, improve production efficiency, and bring economic benefits. At the same time, this method is also conducive to reducing the impact on the environment. By developing high-value utilization methods for coal gasification fly ash, waste resource utilization and recycling can be achieved, and resource utilization efficiency can be improved, which has a positive impact on both the economic and environmental levels.

[0020] (2) The preparation method of the present invention does not require the use of a large amount of oxidizing acid, making the process simpler, greener and more environmentally friendly, and shortening the reaction time. This feature not only reduces production costs, but also improves production efficiency, providing a more feasible approach for large-scale industrial production. In addition, due to the mild nature of the reaction conditions, it can also effectively reduce energy consumption and chemical waste emissions, further reducing the environmental load.

[0021] (3) The persulfate, potassium ferrate and perchloric acid used in the present invention are not only oxidants, but the introduced heteroatoms such as S, Fe and Cl can not only regulate the structure and surface properties of carbon quantum dots, but also improve their photoelectric properties and chemical stability. Among them, persulfate can be used as a strong oxidant to promote the formation of carbon quantum dots and surface functionalization reactions; the introduction of potassium ferrate can increase the conductivity and photocatalytic properties of carbon quantum dots; and perchloric acid helps to improve the light absorption performance and fluorescence quantum yield of carbon quantum dots. Therefore, the introduction of these heteroatoms not only makes carbon quantum dots have richer functions, but also provides a broader space for their application in optoelectronic devices, catalysts and biomedicine. Explanations of the Figures BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a process flow chart for preparing carbon dots using coal gasification fly ash as a carbon source.

[0023] Figure 2 Example 1 is a luminescent photograph of carbon dot suspensions of different concentrations under 365nm ultraviolet light.

[0024] Figure 3 Example 2 is a luminescent photograph of carbon dot suspensions of different concentrations under 365nm ultraviolet light.

[0025] Figure 4It is the photoluminescence spectrum of Example 1 under 350nm excitation.

[0026] Figure 5 This is the photoluminescence spectrum of Example 2 under 341 nm excitation. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1: Take 200 mesh coal gasification fly ash and potassium persulfate in a mass ratio of 1:1 and pour them into a clean beaker filled with distilled water, add 100 mL of distilled water, and ultrasonicate for 0.5h at a frequency of 20kHz at room temperature and pressure. After ultrasonication, add sodium hydroxide for neutralization and adjust the pH to neutral. After vacuum filtration, the filtrate is loaded into a high-pressure reactor shell lined with polytetrafluoroethylene and tightened, placed in a 160 ℃ oven and heated for 5h. After the reactor is cooled to room temperature, take out the solution in the reactor lining, filter it with a microporous membrane with a pore size of 0.22μm, and dialyze it with a dialysis bag with a molecular weight cutoff of 3500Da (change water every 12h, change 3 times), then remove the solvent by a rotary evaporator, and the solid product obtained by rotary evaporation is dispersed in ultrapure water to obtain a purified blue carbon dot aqueous solution. The best excitation wavelength is 350nm and the best emission wavelength is 444nm as tested by a fluorescence spectrometer.

[0029] Example 2: Take 200 mesh coal gasification fly ash and potassium persulfate in a mass ratio of 1:5 and pour them into a clean beaker filled with distilled water, add 100 mL of distilled water, and ultrasonicate for 0.5h at a frequency of 20kHz at room temperature and pressure. After ultrasonication, add sodium hydroxide for neutralization and adjust the pH to neutral. After vacuum filtration, the filtrate is loaded into a high-pressure reactor shell lined with polytetrafluoroethylene and tightened, placed in a 160 ℃ oven and heated for 5h. After the reactor is cooled to room temperature, the solution in the reactor lining is taken out, filtered with a microporous membrane with a pore size of 0.22μm, and dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da (change water every 12h, change 3 times), and then the solvent is removed by a rotary evaporator. The solid product obtained by rotary evaporation is dispersed in ultrapure water to obtain a purified blue carbon dot solution. The best excitation wavelength is 341nm and the best emission wavelength is 460nm as tested by a fluorescence spectrometer.

[0030] Example 3: Take 200 mesh coal gasification fly ash and ammonium persulfate in a mass ratio of 1:1 and pour them into a clean beaker filled with distilled water, add 100 mL of distilled water, and ultrasonicate for 0.5h at a frequency of 20kHz at room temperature and pressure. After ultrasonication, add sodium hydroxide for neutralization and adjust the pH to neutral. After vacuum filtration, the filtrate is loaded into a high-pressure reactor shell lined with polytetrafluoroethylene and tightened, placed in a 190 ℃ oven and heated for 5h. After the reactor is cooled to room temperature, the solution in the reactor lining is taken out, filtered with a microporous membrane with a pore size of 0.22μm, and dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da (change water every 12h, change 3 times), and then the solvent is removed by a rotary evaporator. The solid product obtained by rotary evaporation is dispersed in ultrapure water to obtain a purified blue light carbon dot solution. The best excitation wavelength is 352nm and the best emission wavelength is 454nm as tested by a fluorescence spectrometer.

[0031] Example 4: Take 200 mesh coal gasification fly ash and ammonium persulfate in a mass ratio of 1:5 and pour them into a clean beaker filled with distilled water, add 100mL distilled water, and ultrasonicate for 0.5h at a frequency of 30kHz at room temperature and pressure. After ultrasonication, add potassium hydroxide for neutralization and adjust the pH to neutral. After vacuum filtration, the filtrate is loaded into a high-pressure reactor shell lined with polytetrafluoroethylene and tightened, placed in a 190°C oven and heated for 6h. After the reactor is cooled to room temperature, the solution in the reactor lining is taken out, filtered with a microporous membrane with a pore size of 0.22μm, and dialyzed with a dialysis bag with a molecular weight cutoff of 3500Da (change water every 12h, change 3 times), and then the solvent is removed by a rotary evaporator. The solid product obtained by rotary evaporation is dispersed in ultrapure water to obtain a purified blue light carbon dot solution. The best excitation wavelength is 341nm and the best emission wavelength is 440nm as tested by a fluorescence spectrometer.

[0032] Example 5: Take 200 mesh coal gasification fly ash and potassium ferrate in a mass ratio of 1:1 and pour them into a clean beaker filled with distilled water, add 100 mL of distilled water, and ultrasonicate for 0.5h at a frequency of 20kHz at room temperature and pressure. After ultrasonication, add sodium hydroxide for neutralization and adjust the pH to neutral. After vacuum filtration, the filtrate is loaded into a high-pressure reactor shell lined with polytetrafluoroethylene and tightened, placed in a 160 ℃ oven and heated for 7h. After the reactor is cooled to room temperature, take out the solution in the reactor lining, filter it with a microporous membrane with a pore size of 0.22μm, and dialyze it with a dialysis bag with a molecular weight cutoff of 3500Da (change water every 12h, change 3 times), then remove the solvent by rotary evaporator, and the solid product obtained by rotary evaporation is dispersed in ultrapure water to obtain a purified blue light carbon dot solution. The best excitation wavelength is 352nm and the best emission wavelength is 461nm as tested by fluorescence spectrometer.

[0033] Example 6: Take 200 mesh coal gasification fly ash and potassium ferrate in a mass ratio of 1:5 and pour them into a clean beaker filled with distilled water, add 100 mL of distilled water, and ultrasonicate for 2 hours at a frequency of 20kHz at room temperature and pressure. After ultrasonication, add sodium hydroxide for neutralization and adjust the pH to neutral. After vacuum filtration, the filtrate is loaded into a high-pressure reactor shell lined with polytetrafluoroethylene and tightened, placed in a 190 ℃ oven and heated for 5 hours. After the reactor is cooled to room temperature, take out the solution in the reactor lining, filter it with a microporous membrane with a pore size of 0.22μm, and dialyze it with a dialysis bag with a molecular weight cutoff of 3500Da (change water every 12h, change 3 times), then remove the solvent by rotary evaporator, and the solid product obtained by rotary evaporation is dispersed in ultrapure water to obtain a purified blue light carbon dot solution. The best excitation wavelength is 344nm and the best emission wavelength is 459nm as tested by fluorescence spectrometer.

[0034] Example 7 Take 200 mesh coal gasification fly ash and ammonium perchlorate according to a mass ratio of 1:5 and pour them into a clean beaker filled with distilled water, add 100 mL of distilled water, and ultrasonicate for 0.5h at a frequency of 40kHz at room temperature and pressure. After ultrasonication, add sodium hydroxide for neutralization and adjust the pH to neutral. After vacuum filtration, the filtrate is loaded into a high-pressure reactor shell lined with polytetrafluoroethylene and tightened, placed in a 170 ° C oven and heated for 6h. After the reactor is cooled to room temperature, take out the solution in the reactor lining, filter it with a microporous membrane with a pore size of 0.22μm, and dialyze it with a dialysis bag with a molecular weight cutoff of 3500Da (change water every 12h, change 3 times), then remove the solvent by a rotary evaporator, and the solid product obtained by rotary evaporation is dispersed in ultrapure water to obtain a purified blue light carbon dot solution. After fluorescence spectrometer testing, the optimal excitation wavelength is 349nm and the optimal emission wavelength is 448nm.

Claims

1. A method for preparing carbon quantum dots using coal gasification fly ash as raw material, characterized in that: The coal gasification fly ash is used as raw material, which is first pre-oxidized and then transferred into a hydrothermal reactor and placed in an oven with a pre-set temperature for reaction. After the reaction, the product is filtered and separated to obtain the supernatant. The filtrate is placed in a dialysis bag with a molecular weight cutoff of 3500Da and dialyzed for 3 days. The water is changed every 12 hours. The solution in the dialysis bag is concentrated by vacuum distillation and then freeze-dried to obtain solid carbon quantum dots.

2. The method according to claim 1, wherein the coal gasification fly ash is any one of anthracite gasification fly ash, bituminous coal gasification fly ash and lignite gasification fly ash, and is crushed to a size of 200 or more using a ball mill before use.

3. The method according to claim 1, wherein the oxidant used in the pre-oxidation process is any one of persulfate, potassium ferrate and perchlorate.

4. The method according to claim 1, wherein the pre-oxidation temperature is 25°C to 100°C, preferably 60°C to 80°C.

5. The method according to claim 1, wherein the oven temperature is 140°C to 220°C, preferably 160°C to 190°C.

6. The method according to claim 1, wherein the reaction time of the reactor in the oven is 3 to 8 hours, preferably 5 to 7 hours.

7. The method according to claim 1 further comprises a step of post-treating the obtained carbon quantum dots to improve their performance.

8. The method of claim 1, wherein the carbon quantum dots have a size less than 10 nanometers and exhibit fluorescent properties.

Citation Information

Cited By

  • Method for preparing iron-doped carbon dots from coal gasification fine slag for optical excitation device

    CN121948433A

  • A method for preparing iron-doped carbon dots from coal gasification slag for use in photoexcitation devices.

    CN121948433B